Temperature responsive chemical crosslinkable UV pretreated hydrogel for application to injectable tissue regeneration system via differentiations of encapsulated hMSCs. (January 2017) - Kim, Young-Min; Potta, Thrimoorthy; Park, Keun-Hong; Song, Soo-Chang
Abstract: An injectable hydrogel showing temperature-dependent chemical crosslinking was developed to combine injectabilities of physical hydrogels with dense structures of chemical hydrogels for applications in stem cell delivery-mediated tissue regeneration systems showing easy administration and maintenance of well-dispersed cells within the hydrogel. Hydrophobic methacryl groups were applied to thermosensitive poly(organophosphazenes) to induce temperature mediated hydrophobic interaction and chemical crosslinking. UV pretreated polymer solution showed chemical crosslinking not before injection only after injection into the body even it was already exposed to UV. As this injectable hydrogel showed small pore-sizes, it was guessed cell holding without any adhesive moieties were available and showed the potentials for a cell scaffold. In this study, temperature dependent chemical crosslinking and proliferation and differentiation of the encapsulated hMSCs into various tissues were observed in the hydrogels after injection.